What Am I? Descartes’s Various Ways of Considering the Self - Colin Chamberlain (Journal of Modern Philosophy)
In the Meditations and related texts from the early 1640s, Descartes argues that the self can be correctly considered as either a mind or a human being, and that the self’s properties vary accordingly. For example, the self is simple considered as a mind, whereas the self is composite considered as a human being. Someone might object that it is unclear how merely considering the self in different ways blocks the conclusion that a single subject of predication—the self—is both simple and composite, which is contradictory. In response to this objection, this paper develops a reading of Descartes’s various ways of considering the self. I argue that the best reading of Descartes’s qualified claims about the self, i.e., about the self qua mind or the self qua human being, presupposes an account of the unqualified self, that is, of the self simpliciter. I argue that the self simpliciter is not a mind, and that it is not a human being either. This result might suggest the pessimistic conclusion that Descartes’s view of the self is incoherent. To avoid this result, I introduce a new metaphysical account of the Cartesian self. On my view, the self is individuated by a unified mental life. The self is constituted by the beings that jointly produce this mental life, and derives its unity from it.